114 SURVIVAL OF PATIENTS WITH PULMONARY ARTERIAL HYPERTENSION AND CHRONIC THROMBOEMBOLIC PULMONARY HYPERTENSION LISTED FOR LUNG TRANSPLANTATION. (15th December 2022) - Magnani, Ilenia; Manes, Alessandra; Dolci, Giampiero; Salvaterra, Elena; Daddi, Niccolò; Paganelli, Gian Maria; Antonacci, Filippo; Guarino, Daniele; Dardi, Fabio; Palazzini, Massimiliano; Galiè, Nazzareno; Manes, Alessandra
Abstract: Background: despite the approval of pulmonary arterial hypertension (PAH) specific therapies, bilateral lung transplantation (LT) remains the therapeutic option of choice for patients that fail to reach an adequate clinical and hemodynamic response on maximal medical therapy. Methods: we describe the survival of transplant recipients (TR) patients in comparison to not-transplanted (NT) patients in a single tertiary PAH centre. We included patients with Group 1 PAH and non-operable CTEPH who were listed for lung transplantation at our Centre from January 1999 to February 2022. The survival of NT, TR and of all listed patients was evaluated starting from the date of listing (patients were censored as alive at the time of LT in the intention to treat analysis). The survival of TR was also evaluated starting from the date of the LT. Kaplan Meier curves and log rank test were used for survival analysis. Data are expressed as median (interquartile range). Results: 141 patients were included (80% had Group 1 PAH). Fifty-eight (41%) patients were transplanted, after a mean waiting time of 17 (5-36) months. Of the 83 NT patients 53 (38%) died while on the list and 30 (21%) were alive on the list up to February 2022. The survival of all patients since listing (intention to treat analysis) at 1, 3 and 5 years was 83%, 54%, 45% respectively. The survival of TR at 1, 3, 5 and 10 years since transplantation was 67%, 65%, 62% and 57% respectively. When comparing, NT and TR patients' survival since listing, TR patients had a better survival than NT patients [survival at 1, 3 and 5 years of 88%, 72% and 66% vs 73%, 42% e 34% for TR and NT patients, respectively ( p= 0.0002 )]. Conclusions: our experience demonstrated that TR's survival at our center is in line with principal European national registries and confirmed that the risk of death in the first-year post-transplant is higher for patients with pulmonary hypertension than it is for other diseases which might require LT. Finally, our study showed that the prognosis of patients listed is extremely poor and that, despite biases in the comparison of non-randomized groups, survival of TR is better than the one of NT patients.